Governing Corporate Social Responsibility: An Assessment of the Contribution of the UN Global Compact to CSR Strategies in the Telecommunications Industry - Runhaar, Hens (Journal of business ethics, 2009)
CSR has become an important element in the business strategy of a growing number of companies worldwide. A large number of initiatives have been developed that aim to support companies in developing, implementing, and communicating about CSR. The Global Compact (GC), initiated by the United Nations, stands out. Since its launch in 2000, it has grown to about 2900 companies and 3800 members in total. The GC combines several mechanisms to support CSR strategies: normative principles, networks for learning and co-operation, and communication and transparency about CSR activities. However, up to now only a few empirical evaluations of the contribution of the GC to CSR strategies have been conducted that however have not differentiated between different types of companies (regarding type of industry or regarding the maturity of CSR). This paper aims to partly fill this knowledge gap by a case study examination of three frontrunner companies in the telecommunications industry. The results show that the GC is only one of the many initiatives that these companies employ in shaping, implementing, and reporting about their CSR strategies, and that its role is at most modest. There are two important reasons. One is that many of the CSR issues that these companies deal with are industry specific and are hence addressed in specific networks. The second reason is that the GC principles are perceived as minimum requirements that do not provide many incentives to the three case study companies to perform better. A differentiation of norms for GC members is expected to enhance the contribution of the GC to CSR strategy employment, not only for frontrunner companies but as well for other categories of companies.